2000
DOI: 10.1007/s000240050005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Magnetotelluric Modeling of Smooth 2D and 3D Conducting Bodies Using Rayleigh-Fourier Codes

Abstract: Recently, a method for 3D magnetotelluric modeling was developed, which is based on the application of the Rayleigh scattering theory. This method, RF-3D, is especially capable of modeling multilayered structures with smooth irregular boundaries. The formulation allows inclusion of layers with vertically anisotropic electrical conductivity.Using RF-3D, the response of smooth structures of practical interest is calculated and the importance of 3D effects is evaluated. Two models consisting of a 3D conductive bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Onedimensional interpretation of 2D data is known to introduce "false conducting layers" (Berdichevsky and Dmitriev, 1976) at off-anomaly sites, among other artifacts. Two-dimensional interpretation of 3D data can lead to underestimates of the total conductance (Wannamaker et al, 1984;Martinelli et al, 2000), discussed further below. Interpretation in an incorrect coordinate system will yield erroneous structure in the model.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Onedimensional interpretation of 2D data is known to introduce "false conducting layers" (Berdichevsky and Dmitriev, 1976) at off-anomaly sites, among other artifacts. Two-dimensional interpretation of 3D data can lead to underestimates of the total conductance (Wannamaker et al, 1984;Martinelli et al, 2000), discussed further below. Interpretation in an incorrect coordinate system will yield erroneous structure in the model.…”
Section: Discussionmentioning
confidence: 97%
“…14. Distortion-corrected data from site 005 compared to a 1D model which includes a conducting layer at 100 m with the same conductance as observed in drillhole OK-M3 in the interval 454-470 m. Martinelli et al (2000) undertook a comparison of 2D inversion of 3D data for a problem with an embedded inhomogeneity, and showed that whereas the geometry of the top and sides of the body is reasonably well-recovered, the 2D models underestimated the thickness of the conductor by up to 30% (i.e., underestimate the total conductance by that amount). The TM-mode equivalent model is closest to the true cross-section of the 3D model, but the TE-mode equivalent model is also a reasonable approximation to that cross-section.…”
Section: Validity Of 2d Inversion Of 3d Structuresmentioning
confidence: 99%